2008
DOI: 10.1210/jc.2008-0019
|View full text |Cite
|
Sign up to set email alerts
|

Gluteal Nodules in Patients with Metastatic Midgut Carcinoid Disease Treated with Depot Somatostatin Analogs

Abstract: Patients with metastatic midgut carcinoid tumors have large numbers of asymptomatic sc nodules in the gluteal area when on either depot somatostatin analog, but these resolve over time. This clear observation gives reassurance to patients and those managing them that such nodules are unlikely to represent metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…In a recent publication asymptomatic subcutaneous nodules, on average 1 cm in size, were frequently observed in patients with carcinoid disease following longterm treatment with depot formulations of octreotide and lanreotide, with a tendency to be more common after administration of lanreotide [4]. In another study, biopsy of a nodule at an early stage showed an inflammatory reaction surrounding a cyst of exogenous material, with subsequent development of a foreign-body granuloma [5].…”
Section: Discussionmentioning
confidence: 93%
“…In a recent publication asymptomatic subcutaneous nodules, on average 1 cm in size, were frequently observed in patients with carcinoid disease following longterm treatment with depot formulations of octreotide and lanreotide, with a tendency to be more common after administration of lanreotide [4]. In another study, biopsy of a nodule at an early stage showed an inflammatory reaction surrounding a cyst of exogenous material, with subsequent development of a foreign-body granuloma [5].…”
Section: Discussionmentioning
confidence: 93%
“…They are frequently multiple, often with poorly defined borders and associated with hazy changes in the adjacent subcutaneous fat. 6 These CT findings cannot usually distinguish between SSAs-related nodules and metastases. Sonographic findings have not been previously reported for these nodules.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, CT scans showed nodules associated with SSAs injections to be generally located in the subcutaneous fat of the gluteal region. They are frequently multiple, often with poorly defined borders and associated with hazy changes in the adjacent subcutaneous fat . These CT findings cannot usually distinguish between SSAs‐related nodules and metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations